Involuntary unemployment and the business cycle - Lawrence J. Christiano; Mathias Trabrandt; Karl Walentin (Sveriges Riksbank, 2012)
Can a model with limited labor market insurance explain standard macro- and labor market data jointly? We seek to construct a monetary model in which: i) the unemployed are worse off than the employed, i.e. unemployment is involuntary and ii) the labor force participation rate varies with the business cycle. To illustrate key features of our model, we start with the simplest possible New Keynesian framework with no capital. We then integrate the model into a medium sized DSGE model and show that the resulting model does as well as existing models at accounting for the response of standard macroeconomic variables to monetary policy shocks and two technology shocks. In addition, the model does well at accounting for the response of the labor force and unemployment rate to these three shocks.
Keywords: E2; E3; E5; J2; J6; 330; DSGE; unemployment; labor force participation; business cycles; monetary policy; Bayesian estimation; Dynamisches Gleichgewicht; Unfreiwillige Arbeitslosigkeit; Konjunktur; Phillips-Kurve; Geldpolitik; Bayes-Statistik